Pengukuran Kinerja Rawat Inap Berdasarkan Perspektif Balanced Scorecard - Yangga Dzikrin Nur; Setya Haksama (Universitas Airlangga, 2016)
The 3rd class of inpatient ward in Surya Medika Gresik Hospital had an ideal Bed Occupancy Rate. This rate also had been decreased since 2014. This study is aimed to assess the performance of the 3rd class of inpatient ward based on Balanced Scorecard. This is a descriptive observational study with cross sectional design. Respondents are Chief Inpatient, Head of the Division of Finance and Family Patients. The results of scoring showed that the are only two perspectives that show a positive performance. The learning and growth perspective has 0.9 which means good performance. The internal business process perspective has 1.6 that categorized as very poor performance. The customer focus perspective has 0.25 that categorized as poor performance. The last perspective, financial perspective, valued 0.05 which is good performance. This study suggest to employing cleaning service, making and socialization of Standard Operating Procedure, making the scheme service flow, improving discipline of doctor, holding service quality training, also increasing the intensity of monitoring and evaluation .Keywords: balanced scorecard, performance assessment, scoring